Synchronization of chaotic behavior in nonlinear Bloch equations - Uçar, A; Lonngren, KE; Bai, EW (Elsevier Science Bv, 2003)
Abergel recently demonstrated that the set of nonlinear Bloch equations would admit chaotic solutions for a certain set of numerical values assigned to the system constants and initial conditions [Phys. Lett. A 302 (2002) 17]. We demonstrate in this Letter that two Bloch systems described with different values of system constants and initial conditions can be synchronized together using techniques from nonlinear control theory. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: chaos; synchronization; nonlinear Bloch equations; nuclear magnetic resonance